Clinical Signs of Base of Skull Fracture in the South Indian Population - Jain, Harsh; Ranjan, Shambhavi; Ganesh, Krishnamurthy (Asian Journal of Neurosurgery, 2024)
Objective The clinical signs of base of skull fracture (BSF) are often ambiguous and difficult to identify, but are often used to make decisions on early medical interventions. This study aimed to assess the prevalence of the clinical signs of BSF, their dependency to diagnose this injury and to assess the correlation between the presence of these clinical signs and the severity of head injury and patient outcome.Materials and Methods A cross-sectional study was conducted in a tertiary care hospital in South India over a period of 3 years (2020–2023). Patients older than 18 years, with radiological or surgical evidence of BSF were monitored for developing the clinical signs including Battle's signs, raccoon's sign, otorrhea, and rhinorrhea. The presence of these clinical signs was correlated with demographical characteristics, patient presentation, complications, and their outcome.Results A total of 292 patients were included in the study. The mean age of the cohort was 36.27 ± 18.68 years. A total of 55 (18.8%) showed at least one of the four signs of BSF. Raccoon's sign was seen in 9.5% cases, Battle's sign in 5.5%, otorrhea in 5.5%, and rhinorrhea in 2.4% cases. Patients with frontal (p = 0.021) or ethmoid (0.049) fractures and ENT bleeding (p = 0.022) were significantly more likely to present with at least one sign of BSF. The patients who presented with clinical signs were more likely to have a complication during the course of the hospital stay (p = 0.024) than those without clinical signs, including cranial nerve palsy (p < 0.001) and cerebrospinal fluid leak (p < 0.001). The outcome of the patient did not change based on the presence of clinical signs (p = 0.926).Conclusion These study results indicate a limited diagnostic value of BSF clinical signs in the South Indian population. Thus, other modalities should be considered for the diagnosis when suspected. These results also discourage the use of the nasal route in all patients with suspected head injury and emphasize that during the nasal aspiration procedure, the use of a rigid device is fundamental to avoid false passage of the aspiration tube from the nasal to the intracranial region.
Keywords: raccoon; battle; BSF; fracture; clinical signs; base of skull